Conventional design and numerical analysis of buried cylindrical structure - Gautam, Chetan Kumar (Journal of Structural Engineering, 2024)
A cylindrical buried structure made of two precast Reinforced Cement Concrete (RCC) sections is designed by the conventional method given in Indian Standard (IS) codes. This cylindrical structure is designed as a non-pressure circular RCC pipe. The superimposed load on the structure is high, hence, the strength of standard circular pipe section is increased by taking more wall thickness, higher grade of concrete, extra reinforcement, addition of steel fibres, etc. This cylindrical concrete structure is tested for earth pressure and it was observed that strains and deflections produced in the sections were low. This cylindrical pipe structure is analysed using a two dimensional finite element analysis software package to find out the actual strength of the sections. Detailed numerical analysis of RCC section is given in this paper. In this analysis, various parameters like tensile strength of concrete, soil properties, interfacial contact conditions etc. are changed to check their effects on the results. The results obtained from design using IS code methodology, experimental testing and the numerical analysis using finite element software package are presented in this paper.